2020
DOI: 10.21037/tcr.2020.03.64
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting beads-transcatheter arterial chemoembolization with or without iodine-125 treatment is effective and tolerable in treating advanced non-small cell lung cancer patients: a pilot study

Abstract: Background This study aimed to explore the efficacy and safety of drug-eluting beads-transcatheter arterial chemoembolization (DEB-TACE) with or without iodine-125 ( 125 I) seed implantation in treating advanced non-small cell lung cancer (NSCLC) patients. Methods A total of 25 advanced NSCLC patients underwent DEB-TACE were consecutively enrolled, among which 17 cases also received 125 I seed implantation post DEB-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This treatment could control disease progression and contribute to pulmonary re-expansion over a relatively long period of time ( Shang et al, 2020 ). Improvement of dyspnea would elevate patient quality of life and strengthen confidence for patients with advanced lung cancer after failure of various therapies ( Zhao et al, 2020 ). Comparing the high pulmonary re-expansion rate after airway stent placement as the previous study reported, DEB-BACE would achieve effective pulmonary re-expansion, and meanwhile still locally control tumor growth ( Bi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment could control disease progression and contribute to pulmonary re-expansion over a relatively long period of time ( Shang et al, 2020 ). Improvement of dyspnea would elevate patient quality of life and strengthen confidence for patients with advanced lung cancer after failure of various therapies ( Zhao et al, 2020 ). Comparing the high pulmonary re-expansion rate after airway stent placement as the previous study reported, DEB-BACE would achieve effective pulmonary re-expansion, and meanwhile still locally control tumor growth ( Bi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of DEB-TACE, which employs the use of microspheres to not only serve as carriers of chemotherapy but also as embolization agents, has been shown to be effective in safe in patients with metastatic lung cancer and advanced NSCLC. 91 , 92 A recent retrospective study analyzed 36 patients with lung cancer and hemoptysis who were treated by either DEB-BACE or conventional BACE (cBACE). 68 The analysis found that while there were no significant differences in the technical and clinical successes of hemoptysis treatment ( P > .050), DEB-BACE was associated with increased total clinical response ( P = .021), greater objective response rate ( P = .035), and greater hemoptysis relapse-free survival ( P = .013) when compared to cBACE.…”
Section: Image-guided Transarterial Therapiesmentioning
confidence: 99%